Digital Well-Being: Guidance & Counseling Service Digitalization Program to Reduce Burnout Among Guidance & Counseling Teachers in Singkawang Junior High School - Insan Suwanto; Kamaruddin Kamaruddin; Kasnur Saputra (International Journal of Public Devotion, 2025)
Guidance counselors at junior high schools in Singkawang City face a heavy administrative burden and work pressure that often triggers stress and Burnout. To overcome this problem, efforts to strengthen digital competencies are needed so that guidance services can be more efficient and support the well-being of teachers. The Digital Well-Being Program aims to improve the digital skills of guidance counselors while equipping them with strategies for maintaining work-life balance, thereby reducing administrative burdens and improving mental health. The program is implemented through a series of socialization activities, training, workshops, and assistance with the implementation of digital guidance counseling services. Participants are introduced to the use of technology applications that support guidance counseling services. Practical guidance modules and digital well-being guidelines are also provided to support daily implementation. This program results in guidance counselors with better digital skills, more optimal implementation of technology-based guidance counseling services, and the creation of a work-life balance that supports Burnout reduction. Guidance counseling services become more effective, innovative, and sustainable, thereby having a positive impact on teachers and students. Digital Well-Being: Program Digitalisasi Layanan BK untuk Mengurangi Burnout Guru BK SMP di Kota SingkawangABSTRAKGuru BK SMP di Kota Singkawang menghadapi beban administrasi tinggi dan tekanan kerja yang sering memicu stres dan Burnout. Untuk mengatasi masalah tersebut, diperlukan upaya penguatan kompetensi digital agar layanan BK dapat lebih efisien dan mendukung kesejahteraan guru. Program Digital Well-Being bertujuan meningkatkan keterampilan digital guru BK sekaligus membekali mereka dengan strategi menjaga keseimbangan kerja–kehidupan (work-life balance), sehingga beban administratif berkurang dan kesehatan mental lebih terjaga. Program dilaksanakan melalui serangkaian kegiatan sosialisasi, pelatihan, workshop, dan pendampingan implementasi digitalisasi layanan BK. Peserta diperkenalkan pada penggunaan teknologi aplikasi pendukung layanan BK. Modul panduan praktis dan panduan kesejahteraan digital juga diberikan untuk menunjang penerapan sehari-hari. Program ini menghasilkan guru BK dengan keterampilan digital yang lebih baik, penerapan layanan BK berbasis teknologi yang lebih optimal, serta terciptanya keseimbangan kerja–kehidupan yang mendukung pengurangan Burnout. Layanan BK menjadi lebih efektif, inovatif, dan berkelanjutan sehingga memberi dampak positif bagi guru dan siswa.Kata Kunci :Digitalisasi, Burnout, Guru BK, Digital Well Being, Kota Singkawang